Wii-habilitation as balance therapy for children with acquired brain injury. (23rd November 2012) - Tatla, Sandy K.; Radomski, Anna; Cheung, Jessica; Maron, Melissa; Jarus, Tal
Abstract : Purpose: To evaluate the effectiveness of the Nintendo Wii compared to traditional balance therapy in improving balance, motivation, and functional ability in children undergoing acute rehabilitation after brain injury. Methods: A non-concurrent, randomized multiple baseline single-subject research design was used with three participants. Data were analyzed by visual inspection of trend lines. Results: Daily Wii balance training was equally motivating to traditional balance therapy for two participants and more motivating for one participant. While improvements in dynamic balance were observed, the results for static balance remain inconclusive. All participants demonstrated improvements in functional ability. Conclusion: Wii balance therapy is a safe, feasible, and motivating intervention for children undergoing acute rehabilitation after an acquired brain injury. Further research to examine the effectiveness of Wii balance therapy in this population is warranted.